Data Precision and Timeliness of Paper versus Software-Assisted Nursing Documentation: A Rapid Review and Meta-Analysis - Eleke, Chinemerem; Nwaneri, Ada; Okoronkwo, Ijeoma; Samuel, Joy (Journal of Health Informatics in Africa, 2024)
Background and Purpose: The nursing industry has progressively transitioned from paper-assisted documentation practices to software-assisted systems. Such a transition raises debates about its implications on the timeliness and precision of documented nursing data. This rapid review and meta-analysis examined existing literature on the effect of paper and software-assisted documentation systems on documentation precision and timeliness. Methods: Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, this review and meta-analysis examined studies published in the past 50 years (1973 to 2023) and available in PubMed electronic database. The search methodology combined free-text search terms with Boolean operators for a more precise and sensitive search. Results: The review and meta-analysis selected 15 studies from a pool of 314 articles after applying set inclusion criteria. The synthesis of evidence revealed that Software-assisted nursing documentation systems enhanced by twofold the precision of documented nursing data (Overall random effect Odds Ratio: 2.35, 95% CI: 1.32-4.17; p = < 0.010). Software-assisted nursing documentation systems reduced time spent on nursing documentation by nine minutes but was not significant (Overall random effects mean difference = 9.14 minutes; p = 0.330). Conclusions: Software-assisted nursing documentation is valuable for enhancing nursing documentation precision but not timeliness. This study recommends software-assisted nursing documentation systems for improving the precision of nursing documentation.